Verbal and Non-Verbal Signs of VANS Advertisements - Putra, Agung Mahesa; Marantika, I Made Yogi (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study aims to analyze the verbal and non-verbal signs found in selected VANS advertisements and uncover how these signs communicate messages beyond product promotion. Using a qualitative descriptive method, data were collected through observation of two advertisements sourced from VANS’ official website and social media. The signs were analyzed based on Saussure’s (1983) theory of signifier and signified, Barthes’ (1977) concept of denotation and connotation, and Cerrato’s (2012) theory of color. The findings reveal that nonverbal signs, such as images, color schemes, and layout, appear more frequently and carry stronger connotative meanings than verbal signs. These visual elements were found to convey values such as individuality, youth confidence, and cultural belonging. Verbal signs, such as slogans and product descriptions, support the visual messages by reinforcing brand identity. In conclusion, the study finds that VANS advertisements use a combination of symbolic visuals and concise language to create an emotional and cultural connection with the audience, positioning the brand not only as a product but also as a lifestyle representation.